(3GdLhGeYs - (3eMeO Hf CMeO Hf eMeO Hf QTO GdbQWHj GdCfOdSj, CHh GdhdjO (B((3GdMajO(B)(3,J (B595 (3g` s
(3ChdgG (B:s
(3ebGdGJ GQSWh GdehVhYI ai Yde eG HYO GdWHjYI s
(3BNQgG (B:s
(3gfG fbVi gPG Gdbhd ai GdLRA GdKGfi GdYde s
(3eUOQ GbJfGA GdCUd (B:s
(3CSHGfjG (B- (3eOQjO (B(5000) s
Keywords: (3GdadSaI hGdefWbs